Weaning calves’ response to a medicated top dressing - Fleck, A.A.; Schalles, R.R.; Riley, Jack G.; Fink, G.; O' Banion, D.S. (Kansas State University. Agricultural Experiment Station, 2011)
Adding a medicated top dressing to a weaning calf ration did not reduce calf sickness, but increased weight gains the second and third weeks of a three-week weaning trial.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Weaning; Weight gain